Differential regulation of insulin-like growth factor binding protein-1 and -2 by insulin in the baboon (Papio anubis) endometrium - Fazleabas Asgerally T; Fleming Steven D; Bell Stephen C (BMC, 2008)
Abstract Background The purpose of this study was to examine the effect of insulin on expression and synthesis of IGFBP-1 and IGFBP-2 in the baboon endometrium in vitro. Methods Baboon endometrial explants collected from cycling, ovariectomized, steroid-treated, simulated-pregnant and pregnant animals were cultured for 48 h in the presence or absence of insulin, with or without estradiol, progesterone and hCG. Results Insulin clearly inhibited IGFBP-1 production and mRNA expression in a time- and dose-dependent manner, whereas IGFBP-2 synthesis was not significantly affected. The inhibitory effects of insulin on IGFBP-1 were more evident in explants of non-pregnant tissue or tissue away from the implantation site. In the absence of insulin, synthesis of IGFBP-1 was induced in explants with low levels of de novo synthesis whereas IGFBP-2 synthesis was inhibited. This effect was potentiated by steroids and hCG in the explant cultures. Conclusion Insulin differentially regulates endometrial IGFBP-1 and IGFBP-2 secretion in the baboon.